Equivalent irradiation dose rates in atmosphere during solar flares - Chebakova, E.A. (Recent Contributions to Physics, 2014)
Equivalent irradiation dose rates during solar flares followed by generation of particles of high energies were studied in the present paper. Analysis of irradiation doses at different altitudes at Earth’s atmosphere at the basis of data of spaceships IMP-8, GOES-8 and world network station of neutron monitors is carried out. 36 solar flares (GLE) were analyzed for the period of 1971-2002. Dependencies of equivalent dose rates from geomagnetic cutoff rigidity were determined. Equivalent irradiation dose rates were calculated for different energy ranges of particles: 10 MeV, 90 MeV, 1 GeV. Dependencies of irradiation equivalent dose rates from the depth of Earth’s atmosphere were determined for different energies of particles. Conclusions from the analysis of obtained results says that equivalent dose from strong flares can rise more than 5 times in comparison with the maximum permissible one. Equivalent dose rates are increased with the altitude. Maximum values of irradiation doses during flares on Sun are observed at poles. The raise of equivalent dose rates is caused by the decrease of geomagnetic cutoff rigidity. The obtained data contributes to the prediction of solar cosmic rays.